Effectiveness of Mirror Therapy on Post Stroke Functional Ability: A Meta-Analysis - Galang Aji Samudera; Hanung Prasetya; Bhisma Murti (Indonesian Journal of Medicine, 2023)
Background: Stroke is the third leading cause of death after heart disease and cancer. One of the impacts of stroke is it causes a decrease in the functional ability to carry out daily activities, therefore mirror therapy is carried out to restore the functional ability. The study aims to determine the effect of mirror therapy on the functional ability of post-stroke patients based on previous primary studies.Subjects and Method: It was a systematic review and meta-analysis study with PICO as follows: P= post-stroke patients, I= mirror therapy, C= conventional therapy, and O= functional ability. Data collection was conducted from databases, namely: Google Scholar and PubMed. The inclusion criteria used were full-text articles in English, with randomized control trial design, published in 2006-2021. The keywords used were "stroke" AND "mirror therapy" AND "functional independence measure" OR "FIM" AND "randomized control trial". The inclusion criteria of the study were articles using a randomized control trial study design, the effect size used was the Mean SD, the subjects of the study were patients with poststroke conditions, the intervention given was mirror therapy, the comparison was conventional therapy, with the outcome was increased functional ability. The articles were analyzed using Review Manager 5.3. application.Results: The meta-analysis was conducted on 9 primary studies from several countries such as Turkey, South Korea, India, and Italy. The results of the study showed that there was an effect of mirror therapy on the functional ability of post-stroke patients. Patients who obtained mirror therapy had a functional ability of 0.92 units higher than conventional therapy. The results were statistically significant (SMD= 0.92; 95% CI= 0.67 to 1.17; p<0.001).Conclusion: mirror therapy can improve the functional ability of post-stroke patients.Keywords: mirror therapy, functional ability, post-strokeCorrespondence: Galang Aji Samudera. Master’s Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java, Indonesia. Email: ghalangsamudera@gmail.com. Mobile: +6287836783209.Indonesian Journal of Medicine (2023), 08(01): 1-11https://doi.org/10.26911/theijmed.2023.08.01.01